New Existence Results for Higher-Order Nonlinear Fractional Differential Equation with Integral Boundary Conditions. (20th July 2010) - Feng, Meiqiang; Zhang, Xuemei; Ge, WeiGao
Abstract : This paper investigates the existence and multiplicity of positive solutions for a class of higher-order nonlinear fractional differential equations with integral boundary conditions. The results are established by converting the problem into an equivalent integral equation and applying Krasnoselskii's fixed-point theorem in cones. The nonexistence of positive solutions is also studied.